2014
DOI: 10.1523/jneurosci.1838-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Prostaglandin E2Synthesizing Enzymes in Brain Endothelial Cells Attenuates Inflammatory Fever

Abstract: Fever is a hallmark of inflammatory and infectious diseases. The febrile response is triggered by prostaglandin E 2 synthesis mediated by induced expression of the enzymes cyclooxygenase-2 (COX-2) and microsomal prostaglandin E synthase 1 (mPGES-1). The cellular source for pyrogenic PGE 2 remains a subject of debate; several hypotheses have been forwarded, including immune cells in the periphery and in the brain, as well as the brain endothelium. Here we generated mice with selective deletion of COX-2 and mPGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 34 publications
6
90
1
3
Order By: Relevance
“…However, as we previously reported, the recombination in the brain endothelial cells elicited by the Slco1c1 CreER T2 line may not be complete; when the Cox-2 gene was targeted ϳ15% of the Cox-2 protein induction remained (Wilhelms et al, 2014). It is conceivable that re- maining IL-6R␣ expression in endothelial cells accounts for the residual fever (and Cox-2 expression) seen in the present study.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…However, as we previously reported, the recombination in the brain endothelial cells elicited by the Slco1c1 CreER T2 line may not be complete; when the Cox-2 gene was targeted ϳ15% of the Cox-2 protein induction remained (Wilhelms et al, 2014). It is conceivable that re- maining IL-6R␣ expression in endothelial cells accounts for the residual fever (and Cox-2 expression) seen in the present study.…”
Section: Discussionmentioning
confidence: 44%
“…However, the mechanism by which IL-6 mediates fever is not clear. Whereas studies using genetically modified animals have shown that IL-1 elicits fever by inducing PGE 2 synthesis in brain endothelial cells (Ching et al, 2007;Ridder et al, 2011;Wilhelms et al, 2014), similar functional studies on the role of IL-6 for the febrile response have been lacking. Receptors for IL-6 exist in two forms, a soluble receptor, sIL-6R, and a membrane bound receptor, IL-6R␣.…”
Section: Introductionmentioning
confidence: 99%
“…The critical role of endothelial cells for the PGE2 production that elicits fever has recently also been demonstrated by targeted deletion of COX-2 and mPGES-1 in brain endothelial cells (Wilhelms et al, 2014). Taken together these studies should end a long controversy concerning this issue (Saper et al, 2012).…”
Section: Discussionmentioning
confidence: 79%
“…Two main opposing views emerged, one supporting the endothelial cells (Cao et al, 1995;Ek et al, 2001;Matsumura et al, 1998;Yamagata et al, 2001) and the other favoring the perivascular macrophages (Breder and Saper, 1996;Elmquist et al, 1997a;Schiltz and Sawchenko, 2002). To address this question, we (paper I) Hamzic et al, 2013b;Matsuwaki et al, 2014;Wilhelms et al, 2014) and other groups (Chakravarty and Herkenham, 2005;Ching et al, 2007;Gosselin and Rivest, 2008;Ridder et al, 2011) have developed complex transgenic mice models that allowed in vivo analysis of one gene in a BBB cell population at a time (reviewed with paper I).…”
Section: The Bbb As An Interface For Immune Signal-transductionmentioning
confidence: 99%
See 1 more Smart Citation